Peran Teknologi dalam Revitalisasi Strategi Pembelajaran Ekspositori di Abad ke-21 - Ophilia Lindy Agrecia; Yuwantri Yuwantri; Jessica Putri Mannuela; Margareta Margareta; Geffriyani Wulan Dari; Lelo Lelo; Kalip Kalip (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of technology in revitalizing expository learning strategies in the 21st century. Expository learning strategies are direct teaching methods by teachers with verbal explanations of material, which are effective in conveying factual information but have been criticized for not stimulating critical thinking and not catering to the variety of student learning styles. This study examines how the integration of digital technology and active learning approaches can improve the effectiveness and engagement of students in expository learning. The use of multimedia, digital platforms, and learning management systems (LMS) opens up opportunities for more interactive and collaborative teaching. However, challenges such as unequal access to technology and the management of digital learning must be addressed so that technology can optimally improve the quality of teaching. Curriculum revitalization is also important to align education with industry needs and technological developments, emphasizing the development of practical skills and digital literacy so that graduates are ready to compete in the global job market. This study provides analysis and suggestions for education practitioners to implement more adaptive and effective expository learning strategies in today's digital era.